PELANGGARAN ETIKA PARIWARA INDONESIA DALAM IKLAN BLIBLI DAN GOJEK - Ramadhani, Reihana Bornov; Norfauzi, Rikza; Rama, Taufik Adi; Junaedi, Fajar (Jurnal Bincang Komunikasi, 2024)
This research aims to analyze the ethical violations in advertising that occur in Blibli and Gojek YouTube ads. This research is using a qualitative descriptive method to answer the problem formulation, namely how violations of the Indonesian Advertising Ethics can occur in Blibli and Gojek ads. Qualitative research is a form of research to gain a deeper understanding of the problem phenomena. The findings of this research indicate that there are violations in Blibli and Gojek ads through the use of superlative words, particularly in statements such as "Definitely Free Shipping" and "Most Economical." Therefore, this research provides an in-depth understanding of the importance of tighter supervision and control over ethical violations in advertising to avoid actions that are not in accordance with Indonesian Advertising Ethics regulations.